القضية الكردية بين الحقوق المشروعة والتسامح المأمول: دراسة تحليلية: The Kurdish Issue between Legitimate Rights and Hoped- for Tolerance: Analytical Study - Murshid â€˜Abduhu â€˜Amir, â€˜Abdul Wahab Mahyub; Muhammad â€˜Ali Zarâ€™um, â€˜Abdul Hamid (Online Journal of Research in Islamic Studies, 2020)
This article discusses the definition of the Kurdish issue, the legitimate rights of the Kurdish people in equality, freedom, justice and political participation as fixed rights agreed upon by people, and the call to spread goodness and tolerance and transcend intellectual slides that aim to deepen the dispute between all Muslims and reject bigotry and fanaticism that aims to crack and spilit Islamic societies, and the article aims to shed light on the suffering of the Kurds and their legitimate rights, and to spread tolerance and promote unity among all Muslims. Three methods have been adopted namely the descriptive and analytical methods in addition to the historical method. Among the findings: is that the Kurds are an integral part of the Islamic nation that is united under one God and one Prophet, and that our true religion recognizes all nationalities, preserves their right, and recognizes all Muslim ethnic groups , including the Kurds, to enjoy the full legitimate rights, respect their privacy, and allow the Kurdish people to form their political unity .